Empirical Essays on Monetary Policy Rules and Inflation - Vašíček, Bořek (2009)
This dissertation is divided into four essays, each of them having its own structure and methodological framework. Although each of the essays making the chapters of the thesis is self-contained, their topics are very closely related. Consequently, the reader will be able to follow the thesis in its unity. Essay I is a selective survey of the extensive, mostly theoretic, literature dealing with monetary policy rules. We aim at contextualization of the monetary policy rules in the existing monetary economics literature. We explain the logic, the inspiration and the history of the rules for the monetary policy conduct. We distinguish between instrument rules and targeting rules as two basic categories. Finally, we resume specific issues related to policy rules for small open economies. Essay II studies the logic of short-term interest rate setting pursued by 15 EU countries before and after the launch of the EMU. We employ econometric estimation of the augmented Taylor rule (TR) for individual 15 EU countries and the Euro area. Although a vast empirical evidence is available for the major economies like the US, the UK or Germany, there is an important gap in our understanding of the factors behind the short-term interest rate dynamics in smaller economies. We find that in the period preceding the euro adoption, the TR is a poor representation of monetary policy setting in most EU countries and that many central banks considered decisions made by dominant economies rather than their domestic macroeconomic developments. The analysis of monetary policy rule of the ECB features additional problems related to the heterogeneity of the EMU. We argue that results based on Euro-area aggregated series, commonly presented in empirical studies, are subject to diverse econometric problems. We provide some evidence that the ECB is concerned also with national information and propose quasi-panel analysis as a viable framework.